2003
DOI: 10.1021/jo026627c
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Route to 3‘-Amino-3‘-deoxyadenosine Derivatives and Puromycin Analogues

Abstract: 3'-aminoacylamino-3'-deoxyadenosines, analogues of the antibiotic puromycin, have been synthesized from adenosine. They key 3'-azido derivative 10 was obtained through a 3'-oxidation/reduction/substitution procedure. A modified purification protocol on a larger scale was developed for the oxidation step using the Garegg reagent. The coupling reaction between an Fmoc-l-amino acid and the fully protected form of 3'-amino-3'-deoxyadenosine 11 furnished the aminoacylated compounds 12 in high yields. The puromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…For example, for the synthesis of 3'-deoxyadenosine 5'-carboxaldehyde intermediate (1), we devised an efficient protection-deprotection strategy as shown in Scheme 1. Adenosine (2) was converted in three steps to compound 3, 8,9 by selective 2',5'-disilylation (61% yield), followed by treatment with phenyl chlorothionoformate and 4-dimethylaminopyridine (DMAP) in dichloromethane (60% yield), 10 and subsequent Barton radical deoxygenation reaction at C-3 (85% yield). 11 Compound 3 can be deprotected to cordycepin and this approach represents an excellent method to produce gram quantities of this antiviral compound.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for the synthesis of 3'-deoxyadenosine 5'-carboxaldehyde intermediate (1), we devised an efficient protection-deprotection strategy as shown in Scheme 1. Adenosine (2) was converted in three steps to compound 3, 8,9 by selective 2',5'-disilylation (61% yield), followed by treatment with phenyl chlorothionoformate and 4-dimethylaminopyridine (DMAP) in dichloromethane (60% yield), 10 and subsequent Barton radical deoxygenation reaction at C-3 (85% yield). 11 Compound 3 can be deprotected to cordycepin and this approach represents an excellent method to produce gram quantities of this antiviral compound.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The acetylation was performed under conventional reaction conditions using acetic anhydride in pyridine in the presence of TEA (Scheme 1). N-Acetylation can be readily confirmed by FTIR, since N-and O-acetylation gives a characteristic carbonyl absorption at 1680 and 1750 cm À1 , respectively.…”
Section: Acetylationsmentioning
confidence: 99%
“…24 It has also been demonstrated that this reagent can be used to selectively introduce the TBDMS group on hydroxyl groups in the presence of amino groups. 26,27 Furthermore, highly sterically hindered hydroxyl groups can also be modified by using tert-butyldimethylsilyl triflate (TBDMSOTf) as the reagent and 2,6-lutidine as the base. 28 The main hindrance thus far in using this method on chitosan is that the solvent used for the latter reaction is CH 2 Cl 2 , in which chitosan is insoluble.…”
Section: Introductionmentioning
confidence: 99%
“…The enormous power of the method is revealed in the list of natural product syntheses (or approaches thereto) that have employed -hydroxy-directed reduction of ketones using NaBH(OAc) 3 (or Me 4 NBH(OAc) 3 (in no special order): cyclophellitol, 158 sanglifehrin A, 159 aurisides A and B aglycon, 160 Several groups have reported the -hydroxyl-directed reduction of various ketonucleosides. [188][189][190][191][192][193][194][195][196] Simple systems also undergo this stereoselective reduction (e.g., 65), 197 and the method has been applied to the synthesis of polypropionates. 198 Although a chairlike transition state (Scheme 10) does not operate in the acylborohydride reduction of R-hydroxy ketones, these substrates nevertheless can be reduced via intramolecular hydride delivery leading to syntheses of allopumiliotoxin A, 199 the bruceantin quassinoids, 200 and the rocaglamides 201 (Scheme 12).…”
Section: Hydroxy-directed Reduction Of Ketonesmentioning
confidence: 99%